SURGICAL ENDOSCULAR TREATMENT OF NECROTIC ENTEROCOLITIS IN INFANTS (Western European Journal of Medicine and Medical Science, 2025)
Necrotic enterocolitis (NEK) in infants is one of the most severe and common diseases in neonatal surgery. This condition develops more often in premature and low-birthweight children and is characterized by high mortality. In severe stages of the disease, conservative treatment is ineffective, and surgical endoscopic treatment is required. Surgical measures mainly consist of resection of the necrotic part of the intestine and ileostomy. In some cases, intestinal continuity is also restored through anastomosis. During surgical treatment, the child's general condition, metabolic status, and risk of infection should be constantly monitored. Modern clinical protocols recommend surgical treatment in combination with a comprehensive approach, resuscitation support, and continuous rehabilitation. The correct and timely use of surgical methods in NEC is crucial for the survival and further development of the child